计算:若a+b=1,a-b=-2010,则a^2-b^2=?

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/21 09:33:42
计算:若a+b=1,a-b=-2010,则a^2-b^2=?
xSN@~ORҍ]|I`A!?EH8phB< 4ȶWpU{~3ͷN5C.ct%T ͞^W :ib?8&0#Q6)G,,TR5E~,H 21iZY=*,'S,+vDiOVo)hB D`EX,fݓ4Fy'/|a<)=s8u ЭqA̿\XĉOOQbҡFk׶R5(' a1L0@I xw=~lydJ*bvޣP0HY;u-?Lb?y-n)Oꅣ

计算:若a+b=1,a-b=-2010,则a^2-b^2=?
计算:若a+b=1,a-b=-2010,则a^2-b^2=?

计算:若a+b=1,a-b=-2010,则a^2-b^2=?
a^2-b^2是平方差
a^2-b^2=(a+b)*(a-b)=-2010

a+b=1,a-b=-2010
a^2-b^2=(a-b)^2=a^2-b^2+2ab=(a+b)×(a-b)+2ab=-2010+2ab
a^2-b^2=(a+b)^2=a^2+2ab+b^2
a^2-b^2=(a+b)^2-4ab
即为(a-b)^2+4ab
=-2010+2ab+4ab=6ab-2010
(a+b)^2+(a-b)^2=2a^2...

全部展开

a+b=1,a-b=-2010
a^2-b^2=(a-b)^2=a^2-b^2+2ab=(a+b)×(a-b)+2ab=-2010+2ab
a^2-b^2=(a+b)^2=a^2+2ab+b^2
a^2-b^2=(a+b)^2-4ab
即为(a-b)^2+4ab
=-2010+2ab+4ab=6ab-2010
(a+b)^2+(a-b)^2=2a^2+2b^2
突然发现思路错了,重来!
a²-b²=(a+b)(a-b)=2010
a+b=1
所以a-b=2010÷(-1)=-2010
所以(a-b)^2=(-2010)^2
(a+b)^2=1
(a+b)^2+(a-b)^2=2a^2+2b^2
所以2(a^2+b^2)=(-2010)^2+1,
总结论:a^2-b^2=【(-2010)^2+1]/2
(这是补充的

收起

a^2-b^2
=(a+b)(a-b)
=1*(-2010)
=-2010